Literary Cinematography as a Narrative Strategy in a Fiction Text (E. Canetti “Voices of Marrakech”) - E. M. Shastina; Yu. K. Kazakova (Научный диалог, 2023)
The work of the Austrian writer, Nobel Prize winner Elias Canetti (1905—1994) is studied in the aspect of literary cinematography, indicating the synthesis of literature and cinema, in particular, in the choice of means for implementing audiovisuality in a literary text. The phenomenon under study is considered on the material of the book “Voices of Marrakesh. Notes after a Journey” (“Die Stimmen von Marrakesch. Aufzeichnungen nach einer Reise”), the composition of which uses the montage principle, which combines fourteen chapters into a single whole. An attempt was made to identify the originality of Canetti’s idiostyle from the perspective of literary cinematography, which determines the novelty and relevance of the study. The authors proceed from the fact that literary cinematography can be considered as a narrative strategy that includes not only communication with the reader, but also “auto-communication” (Yu. M. Lotman). The question is raised about the significance of the acoustic element (“acoustic mask”) in creating the image of a foreign culture, linguistic means of realizing cinematography are revealed. The methodological basis of this article is the research of domestic and foreign scientists concerning both the narrative nature of a literary text and literary cinematography.